2019
DOI: 10.1016/j.clcc.2019.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Tumor Response and Tumor-Related Symptoms in RAS Wild-Type Metastatic Colorectal Cancer: Retrospective Analyses From 3 Panitumumab Trials

Abstract: Tumor-related symptoms can affect treatment choices in metastatic colorectal cancer (mCRC). In the current study, 659 patients with RAS wild-type mCRC were retrospectively analyzed to evaluate the relationship between tumor shrinkage and the time to onset of tumor-related symptoms. Symptom onset was delayed in patients with earlier and greater tumor shrinkage. Therefore, treatments that facilitate cytoreduction may delay symptom development. Background: There is no standardized assessment of symptomatic events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This exploratory analysis used the EORTC questionnaire and found that ETS was associated with less deterioration of GHS/QOL and functioning. In a retrospective analysis of data from three trials of first-line chemotherapy plus the anti-EGFR antibody panitumumab in RAS -wild-type mCRC, the onset of new tumor-related symptoms, defined as new opiate use, weight loss, anemia, asthenia, and decline in ECOG PS, was delayed by achieving ETS, regardless of the treatment regimen received [ 36 ]. These findings suggest that HRQOL may remain relatively constant in mCRC patients with ETS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This exploratory analysis used the EORTC questionnaire and found that ETS was associated with less deterioration of GHS/QOL and functioning. In a retrospective analysis of data from three trials of first-line chemotherapy plus the anti-EGFR antibody panitumumab in RAS -wild-type mCRC, the onset of new tumor-related symptoms, defined as new opiate use, weight loss, anemia, asthenia, and decline in ECOG PS, was delayed by achieving ETS, regardless of the treatment regimen received [ 36 ]. These findings suggest that HRQOL may remain relatively constant in mCRC patients with ETS.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the objective response rate is not a reliable surrogate for PFS or OS [ 38 ]. On the other hand, ETS is defined as a minimum tumor reduction of 20% 6–8 weeks after the initiation of treatment, and it has been found to be associated with favorable prognostic outcomes in post hoc analyses in several trials, independent of the agents used and cancer types [ 16 , 18 , 28 , 29 , 31 , 36 , 37 , 39 46 ]. We confirmed that ETS was significantly associated with prolonged PFS, OS, and TTF.…”
Section: Discussionmentioning
confidence: 99%
“…15 Early characterization of response can enable key treatment decisions to be taken sooner (eg, a change of therapy for non-responders, particularly for right-side disease, or early planning of surgical intervention, particularly in candidates for liver resection), potentially leading to less exposure to systemic therapy for patients. Early and deep responses to treatment may provide patients with relief from tumor-related symptoms 40 and enable surgical resection to be performed. There are major benefits to be gained from resecting tumors earlier: resection can provide long-term, relapse-free survival or cure, while reduced long-term cancer therapy lowers the occurrence of adverse effects such as liver toxicity and complications of surgery.…”
Section: Discussionmentioning
confidence: 99%